2010
DOI: 10.1371/journal.pone.0008553
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Antigenic Structure of the Pandemic (H1N1) 2009 Influenza Virus Hemagglutinin

Abstract: The pandemic influenza virus (2009 H1N1) was recently introduced into the human population. The hemagglutinin (HA) gene of 2009 H1N1 is derived from “classical swine H1N1” virus, which likely shares a common ancestor with the human H1N1 virus that caused the pandemic in 1918, whose descendant viruses are still circulating in the human population with highly altered antigenicity of HA. However, information on the structural basis to compare the HA antigenicity among 2009 H1N1, the 1918 pandemic, and seasonal hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
181
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(188 citation statements)
references
References 26 publications
7
181
0
Order By: Relevance
“…Previous studies have also reported dominant circulation of this strain worldwide and suggested this is a consequence of enhanced viral fitness. 9,10 Within HA1, there was no evidence of evolutionary trends, in agreement with the genetic and antigenic homogeneity of A(H1N1)pdm09. 11 The location of amino acid substitutions observed in HA1 however, suggests these could result in phenotypic changes; the D222E substitution is located within a loop of the receptor-binding site, A73T and S185N within the putative antigenic sites Cb and Sb, respectively, and K119N has been reported to result in creation of a potential N-glycosylation site.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies have also reported dominant circulation of this strain worldwide and suggested this is a consequence of enhanced viral fitness. 9,10 Within HA1, there was no evidence of evolutionary trends, in agreement with the genetic and antigenic homogeneity of A(H1N1)pdm09. 11 The location of amino acid substitutions observed in HA1 however, suggests these could result in phenotypic changes; the D222E substitution is located within a loop of the receptor-binding site, A73T and S185N within the putative antigenic sites Cb and Sb, respectively, and K119N has been reported to result in creation of a potential N-glycosylation site.…”
Section: Discussionsupporting
confidence: 53%
“…11 The location of amino acid substitutions observed in HA1 however, suggests these could result in phenotypic changes; the D222E substitution is located within a loop of the receptor-binding site, A73T and S185N within the putative antigenic sites Cb and Sb, respectively, and K119N has been reported to result in creation of a potential N-glycosylation site. 9,12 Correlation of these mutations with particular phenotypes, binding specificity or clinical outcome of infection however, needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of antigenic drift, accumulation of glycosylation on the head of HA may mask or modify neutralizing epitopes on the HA surface (24,58). Recent seasonal H1N1 viruses carry three to five sites of N-linked glycosylation on the globular head of HA, whereas SC1918 and Cal/09 A(H1N1) pdm viruses have a single site at Asn 104 (25)(26)(27)59). The HA molecules expressed by H1N1 viruses from the 1930s (NWS/33, WS/33, and PR8/34) used in our studies were poorly glycosylated and, accordingly, all strains were resistant to SP-D and MBL.…”
Section: Discussionmentioning
confidence: 99%
“…Since their appearance in the human population in 1968, H3N2 subtype viruses have shown a progressive increase in N-linked glycosylation (24,25) and recently circulating strains generally carry six to seven potential sites in the globular head region of HA. Recent seasonal H1N1 viruses carry four to five N-glycosylation sequons on the head of HA (25,26) compared with the prototypic 1918 H1N1 pandemic strain A/ South Carolina/1/18 (SC18), which carried a single site (27). Previous studies have shown that increased glycosylation of H3 subtype viruses correlated with enhanced susceptibility to rodent SP-D and MBL and reduced virulence in mice (15,28), although highly glycosylated viruses could elicit severe disease in SP-Ddeficient mice (28).…”
Section: S Ince April 2009 a Global Outbreak Caused By The Novel Panmentioning
confidence: 99%
“…Current S-OIV (2009 H1N1 influenza virus) is a triple reassortment (in terms of host-origin) of influenza gene segments, with PA and PB2 from avian, PB1 from human and HA, NP, NS, NA and M from classical/Eurasian swine (Dawood et al, 2009;Smith et al, 2009;Gao and Sun, 2010). This current H1N1 virus has been found to have many similar properties to the 1918 pandemic H1N1 virus, including the overall similarity of the genome and characteristics of pathogenesis (Itoh et al, 2009;Shen et al, 2009;WHO, 2009;Yang et al, 2009;Igarashi et al, 2010;Yeping Sun et al, 2010).…”
Section: Introductionmentioning
confidence: 99%